CULTURAL REPRODUCTION OF GENDER DIVISION OF LABOR IN IRAYA MANGYAN COMMUNITIES: Implications to Community Development Practice - Bawagan, Aleli B. (Philippine Journal of Social Development; 2008, 2010)
The Iraya Mangyans are the indigenous peoples in the uplands of Northern Mindoro, Southern Luzon, Philippines. They have a distinct culture, such as language, farming practices, spiritual beliefs, customary laws and a social organization apart from the lowland political organization and hierarchy.  Over the years, the Iraya Mangyans have experienced varying changes in their culture and practices brought about by external influences such as the entry of various institutions into their communities which bring in new ideas and ways of doing.